Global Health and Emergency Care: A Resuscitation Research Agenda - Part 2 - Ong, Marcus; Aufderheide, Tom; Nichol, Graham; Bobrow, Bentley; Bossaert, Leo; Cameron, Peter; Finn, Judith; Jacobs, Ian; Koster, Rudolph; McNally, Bryan; Ng, Yih; Shin, Sang; et al. (Wiley Publishing, 2013)
At the 2013 Academic Emergency Medicine global health consensus conference, a breakout session to develop a research agenda for resuscitation was held. Two articles are the result of that discussion. This second article addresses data collection, management, and analysis and regionalization of postresuscitation care, resuscitation programs, and research examples around the world and proposes a strategy to strengthen resuscitation research globally. There is a need for reliable global statistics on resuscitation, international standardization of data, and development of an electronic standard for reporting data. Regionalization of postresuscitation care is a priority area for future research. Large resuscitation clinical research networks are feasible and can give valuable data for improvement of service and outcomes. Low-cost models of population-based research, and emphasis on interventional and implementation studies that assess the clinical effects of programs and interventions, are needed to determine the most cost-effective strategies to improve outcomes. The global challenge is how to adapt research findings to a developing world situation to have an effect internationally.